2006
DOI: 10.1136/jmh.2006.000238
|View full text |Cite
|
Sign up to set email alerts
|

A silly expression: Consultants’ implicit and explicit understanding of Medical Humanities. A qualitative analysis

Abstract: The term Medical Humanities has still not been established in the wider medical, educational and academic communities. This qualitative study, conducted across three acute care trusts, is an exploration of whether clinicians were familiar with the term Medical Humanities, and if so, what the term meant to them and whether they considered the associated concepts relevant to medical practice and education. Reactions to the term Medical Humanities were varied: many clinicians had not heard of the term before, som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Despite the dominance of technical, rational, and efficiency-based priorities in contemporary medicine and medical education, the culture of medicine is not a monolithic entity and no longer speaks with a single voice. For example, a recent study 41 concluded that although many physicians responded to the term "medical humanities" with reactions of uncertainty or even contempt, in fact the goals of medical humanities-particularly those involving increased personal and professional awareness and self-critique-and the goals of the physicians interviewed in terms of fostering professionalism and professional identity, were very similar. This suggests an underlying commonality of interest uniting medical humanities and medicine.…”
Section: Training Cross-disciplinary Reflection About Medicinementioning
confidence: 99%
“…Despite the dominance of technical, rational, and efficiency-based priorities in contemporary medicine and medical education, the culture of medicine is not a monolithic entity and no longer speaks with a single voice. For example, a recent study 41 concluded that although many physicians responded to the term "medical humanities" with reactions of uncertainty or even contempt, in fact the goals of medical humanities-particularly those involving increased personal and professional awareness and self-critique-and the goals of the physicians interviewed in terms of fostering professionalism and professional identity, were very similar. This suggests an underlying commonality of interest uniting medical humanities and medicine.…”
Section: Training Cross-disciplinary Reflection About Medicinementioning
confidence: 99%
“…These perceptions can remain static as students transition into professional roles and view MH with ambiguity or contempt (Knight, 2006).…”
Section: Still Mh Faces Substantial Challenges In Moving Out Of Whatmentioning
confidence: 99%
“…In the medical school curriculum, the medical humanities are intended to promote a way of being that incorporates personal convictions about one's obligations to others and to the development of a professional identity as a humanistic physician with personal attributes such as compassion, engagement, integrity, respect for patients, and a commitment to their own human flourishing (19,20).…”
Section: Emphasizing Humanities In Medical Education To Foster Medicamentioning
confidence: 99%